Research and Development of a Small-Scale Icing Wind Tunnel Test System for Blade Airfoil Icing Characteristics - Lei Shi; Fang Feng; Wenfeng Guo; Yan Li (International Journal of Rotating Machinery)
In order to study the icing mechanism and anti-icing technology, a small low-speed reflux icing wind tunnel test system was designed and constructed. The refrigeration system and spray system were added to the small reflux low-speed wind tunnel to achieve icing meteorological conditions. In order to verify the feasibility of the test system, the flow field uniformity, temperature stability, and liquid water content distribution of the test section were tested and calibrated. On this basis, the icing tests of an aluminium cylinder, an NACA0018 airfoil, and an S809 airfoil were carried out, and the two-dimensional ice shape obtained by the test was compared with the two-dimensional ice shape obtained by the numerical simulation software. The results show that in the icing conditions and icing time studied, the parameters of the test system are stable, and the experimental ice shape is consistent with the simulated ice shape, which can meet the needs of icing research.